John Locke: The Construction of Knowledge in the Perspective of Philosophy - Juhansar Juhansar (Undiksha, 2021)
Epistemology is one of three philosophical dichotomies that rises to two main isms to obtain knowledge: rationalism initiated by Rene Descartes (1596-1650) and empiricism initiated by John Lock (1632-1704). As an empiricist, Locke offers the tabula rasa theory to support his argument. Thus, this study aims to describe radically and comprehensively the concept of John Locke's thought from the perspective of epistemological philosophy. This aim is achieved by describing the background and principal works of John Lock on the philosophy of epistemology, including the main ideas, views, and reasoning of his empiricism through tabula rasa theory. The method used in this research is descriptive qualitative in the field of philosophy. Data were collected through a literature study, then analyzed hermeneutically with two methodical elements: verstehen and interpret. First, this research shows that knowledge is principally obtained from sensory experience in which the mind is only passive. Second, the sensory experience is obtained objectively (primary quality) and subjectively (secondary quality). Third, external sensation and internal sensation obtained from sensory experience are built into simple ideas to complex ideas.